اجراءات الحجز الاحتياطي في القانون العراقي والقانون القطري - لفلوف كوثر عطيه (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Precautionary seizure is a means to oblige the debtor to pay. The creditor resorts to it with the intention of wasting the debtor’s opportunity to smuggle his money or dispose of it at the creditor’s expense based on that. Seizure is regulated by its provisions and procedures in the Civil Procedure Law No. 83 of 1969 amended in Articles (231-250), and not executive seizure, the provisions of which are regulated by the Implementation Law, because precautionary seizure is placed in exchange for a debt: the subject of the dispute in which the judiciary has not spoken its word, and as for executive seizure It is a response to a judicial ruling that has acquired the degree of absoluteness, where the right in question is realized from existence, a certain amount at the time of performance, and does not conflict with public order and morals. The basic principle is that all of the debtor’s money is a guarantee for the performance of his debts, and the debtor’s will is not considered to prevent seizure of some of his money unless the law approves this. For purposes related to public order, humanitarian, economic or financial objectives. The precautionary seizure does not turn into an executive seizure except after all the elements of the executive seizure are fulfilled. Also, the notification of the lawsuit regarding the validity of the seizure does not include a warning to implement the executive seizure, and the executive confiscation does not become such until all its components are completed in accordance with what the law stipulates. It is considered the best way to preserve the debtor’s money by keeping it under the control of the judiciary to collect the right to its price. The creditor also resorts to requesting the imposition of a precautionary seizure on the debtor’s money to which he has a right. granted to him by law, and for execution requires a court order to confiscate every creditor in his possession with an official or ordinary bail, even if there is no document, or if the claim is something that can be proven by witnesses. The law took into account the interest of the debtor, so the investigator surrounded the precautionary seizure with several guarantees to prevent malicious seizures. Precautionary seizure is a precautionary measure and a precautionary measure issued by the judge based on a request from the creditor whose debt has become due for payment. The Qatari legislator stipulated in Article (317) of the Procedural Procedures Law that precautionary seizure is carried out in the above-mentioned cases by decision of the urgent matters judge whose jurisdiction falls on the funds to be seized or in any of the departments if the money is located in more than one department and the seizure request is rejected. automatically. In the event of a lack of local jurisdiction... it can be concluded from this article that the Qatari legislator made the issue of placing pretrial detention before the locally competent court an issue related to public order, contrary to the old procedural law. Pretrial detention is considered one of the important and dangerous procedures in the conduct of the criminal case, and one of the requirements of the investigation and a basic pillar in the preliminary investigation stage. Executive detention in Iraqi law in Article 8 of Iraqi Law No. (23) of 2005 stipulates that forced execution is not permissible except with an executive document in order to provide for the rights of Certain in its existence, specific in its edges, and specific in its amount and state of performance. Executive documents are judgments, decisions, judicial, statutory and Sharia orders, minutes of settlement and reconciliation ratified by regular and Sharia courts, enforceable arbitrators’ rulings, official and customary bonds, and other documents given this status by law. Then we find that precautionary seizure is better than executive seizure in Iraqi law.